Optimal design of two-degree-of-freedom control scheme for non-minimum phase processes with time delay. (2017) - Zhang, Wei; Xia, Lingyue
This paper proposes an analytical two-degree-of-freedom (TDOF) control scheme for non-minimum phases systems with time delay, which leads to remarkable improvement of regulator capacity for both of reference input tracking and input load disturbance rejection. All controllers that make the closed-loop system internally stable and have no steady-error have been employed firstly. Then, the set-point tracking controller and the disturbance rejection controller are analytically derived in terms of the integral squared error performance specifications. The nominal set-point response is decoupled from the load disturbance response in the adopted TDOF control scheme. In consequence, both of the set-point tracking performance and load disturbance rejection performance can be optimised simultaneously and separately. Finally, an illustrative example is included to demonstrate the superiority of the proposed method.